Fabrication of Gamma-Ray Shielding Using Rapid Breakdown Anodization - Hakim, H.; Mohammed, A.N.; Hashim, M.S. (Acta Physica Polonica A, 2023)
The  rapid  breakdown  anodizing  method  was used  to  produce  (Bi, Bi2O3), (Pb, PbO2), and WO3 nanoparticles. These particles are utilized to fabricate gamma-ray shielding. The X-ray diffraction test displayed polycrystalline structures for all samples. Scanning electron microscope images illustrated the formation of (Bi, Bi2O3) and (Pb, PbO2) nanoplates and WO3 semi-sphere particles. Pressures of 318, 477, and 636 MPa were applied to reduce vacancies within the prepared powders and increase their densities. Cylindrical samples with a diameter of 14 mm and different thicknesses were formed. Utilizing gamma rays produced by sources like Am-241 (59.54 keV), Cs-137 (661.6 keV), Co-60 (1173 keV), and Co-60 (1332 keV), the shielding characteristics of the manufactured samples were studied. The linear attenuation coefficient, mass attenuation coefficient, and half-value layer were determined after the gamma flux was measured using a NaI(Tl) detector. The two attenuation coefficients were functions of the source energy, and they had the highest values for (Pb, PbO2) and the lowest for the WO3 sample. The atomic numbers of the elements used and the size of the voids inside the prepared powders played the greatest role in determining the values of the shielding parameters.